2013
DOI: 10.2298/jas1302117m
|View full text |Cite
|
Sign up to set email alerts
|

In vitro sterilization procedures for micropropagation of ‘oblacinska’ sour cherry

Abstract: Surface sterilization is the most important step in preparation of explants for micropropagation, because controlling fungal and bacterial contamination of woody plant from field sources is very difficult. Six sterilizing agents: sodium hypochlorite (NaOCl), calcium hypochlorite [Ca(ClO) 2 ], sodium dichloroisocyanurate (DICA), mercuric (II) chloride (HgCl 2), silver nitrate (AgNO 3) and hydrogen peroxide (H 2 O 2) were tested for sterilization of 'Oblačinska' sour cherry buds, by varying their concentration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
53
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 18 publications
9
53
1
2
Order By: Relevance
“…The step can be undertaken by using different agents like calcium hypochlorite, sodium hypochlorite, ethanol, mercuric chloride, hydrogen peroxide or silver nitrate [36]. Generally, the type of the explants showed the main component where internodes were more preferred compared to the shoots apex.…”
Section: Discussionmentioning
confidence: 99%
“…The step can be undertaken by using different agents like calcium hypochlorite, sodium hypochlorite, ethanol, mercuric chloride, hydrogen peroxide or silver nitrate [36]. Generally, the type of the explants showed the main component where internodes were more preferred compared to the shoots apex.…”
Section: Discussionmentioning
confidence: 99%
“…They used two sterilizing agents, NaOCl(1%) and HgCl 2 (0.1%) with three time duration 2, 5 and 8 minutes, and found that NaOCl for 8 minute was better for controlling the infection and had not any adverse effect on explants even in long duration.On the other hand, [19]reported that both sterilizing agents, HgCl 2 and NaOCl, were effective in making clean explants of Kinnow tree. Nevertheless, [20]showed treatment with sodium hypochlorite (NaOCl), calcium hypochlorite Ca(ClO) 2 and (HgCl 2 ) showed satisfactory results and [21] also showed that the best sterilizing agents were 3% HgCl 2 , 3% NaOCl which reduced bacterial contaminations up to 95%.…”
Section: Effect Of Different Sterilization Methods On Contamination Amentioning
confidence: 99%
“…Many sour cherry cultivars are known as continental cultivars (Ganopoulos et al., ; Grafe & Schuster, ; Homoki et al., ; Khoo et al., ; Papp et al., ; Pissard et al., ; Siddiq et al., ; Viljevac et al., ; Wojdyło et al., ), mainly grown in north and middle European countries (Clausen et al., ; Khoo et al., ; Wojdyło et al., ) as well as in Balkan region (Mihaljević et al., ). On the other hand, there are cultivars that achieve its best quality in Mediterranean climate conditions, like autochthonous cultivar Maraska grown in Dalmatia region (Levaj et al., ; Pedisić, Dragović‐Uzelac, Levaj, & Škevin, ; Repajić et al., ; Viljevac et al., ; Viljevac Vuletić et al., ).…”
Section: Introductionmentioning
confidence: 99%